Notice of an ancient Celtic Brooch, the property of William Rose Campbell (Proceedings of the Society of Antiquaries of Scotland, 1854)
An account of a brooch owned by the Ballochyle family which the family acquired when the Laird of Ballochyle married the daughter of Lamont of Lamont. It is accompanied by a plate with a lithograph of the brooch.